Tilt : shifting your strategy from products to customers - Dawar, N. (Niraj) (Boston, Massachusetts : Harvard Business Review Press, 2013)
"Do you know what your customers want? Renowned Marketing professor Niraj Dawar argues that most companies still look for competitive advantage where it used to be: through activities related to new product creation. But today's advantage comes from interactions of a different sort--those you have with your customers. Only companies that recognize and move on this shift will win out in the end. According to Dawar, a professor at the Ivey Business School in Canada, three critical aspects of business have caused this "downstream" shift: the locus of competitive advantage, the locus of activities that add value (those the customer is willing to pay for), and the primary fixed costs in the business. These changes have profound implications for strategy and on the way businesses are measured, monitored, and managed. So as power shifts "downstream," to where your company interacts with your customers, senior executives and marketers need to understand this new dynamic and reorient your strategy. In fact, most will need to completely shift the center of gravity of the business. Dawar will show you how"--
Keywords: Customer relations; Consumer behavior; Marketing research; Strategic planning; Marketing -- Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Marketing / General